The SCUBA-2 web survey: I. Observations of CO(3–2) in hyper-luminous QSO field. Issue 1 (13th February 2019) - Hill, Ryley; Chapman, Scott C; Scott, Douglas; Smail, Ian; Steidel, Charles C; Krips, Melanie; Babul, Arif; Berg, Trystyn; Bertoldi, Frank; Gao, Yu; Lacaille, Kevin; Matsuda, Yuichi; et al.
Abstract: A primary goal of the Submillimetre Common User Bolometer Array-2 web survey is to perform tomography of the early intergalactic medium by studying systems containing some of the brightest quasi-stellar objects (QSOs; 2.5$\, {\lt }\, z\, {\lt }\, $ 3.0) and nearby submillimetre galaxies (SMGs). As a first step, this paper aims to characterize the galaxies that host the QSOs. To achieve this, a sample of 13 hyper-luminous ($L_{\rm AGN}\, {\gt }\, 10^{14}\, {\rm L}_{\odot }$ ) QSOs with previous submillimetre continuum detections were followed up with CO(3–2) observations using the NOrthern Extended Millimeter Array interferometer. All but two of the QSOs are detected in CO(3–2); for one non-detection, our observations show a tentative 2σ line at the expected position and redshift, and for the other non-detection we find only continuum flux density an order of magnitude brighter than the other sources. In three of the fields, a companion potentially suitable for tomography is detected in CO line emission within 25 arcsec of the QSO. We derive gas masses, dynamical masses, and far-infrared luminosities, and show that the QSOs in our sample have similar properties compared to less luminous QSOs and SMGs in the literature, despite the fact that their black hole masses (which are proportional to L AGN ) are 1–2 orders of magnitude larger. We discuss two interpretations of these observations: this is due to selection effects, such as preferential face-on viewing angles and picking out objects in the tail ends of the scatter in host-galaxy mass and black hole mass relationships; or the black hole masses have been overestimated because the accretion rates are super-Eddington.